A refined cohesive zone model that accounts for inertia of cohesive zone of a moving crack. (September 2016) - Wu, J.; Ru, C.Q.
Highlights: A simple mass-spring cohesive zone model. Mass distribution of cohesive zone defined by an elliptical function. Inertia effect of cohesive zone on dynamic fracture energy. A limiting terminal crack speed above that fracture energy practically tends to infinity. Abstract: Existing cohesive zone models assume that actual fracture zone of non-zero mass can be modeled by a line segment (cohesive zone) with no mass and inertia. In the present work, a simplified mass-spring model is presented to study inertia effect of cohesive zone on a mode-I steady-state moving crack. It is showed that fracture energy predicted by the present model increases dramatically when a finite limiting crack speed is approached. Reasonable agreement with known experiments indicates that the present model has the potential to catch the inertia effect of cohesive zone which has been ignored in existing cohesive zone models and better simulate dynamic fracture at high crack speed.